An Oblate Spheroid Base Isolator and Floating Surface Diaphragm for Seismic Protection of Liquid Storage Tank. Issue 10 (27th July 2022) - Rawat, Aruna; Matsagar, Vasant
ABSTRACT: Base shear and sloshing response control in ground-supported circular cylindrical liquid storage tank is achieved by oblate spheroid base isolation (OSBI) system used along with floating surface diaphragm on the contained liquid. The new base isolation system, OSBI proposed herein is based on rolling-friction mechanism in ellipsoidal-shaped isolators in both the horizontal axes. The surface diaphragm is proposed to float on the free liquid surface to control the sloshing amplitude. The tank is analyzed using the coupled acoustic-structural (CAS) approach in finite element method (FEM). In order to have conformity of the present FE model, the FEM results are compared with the mechanical lumped-mass model of the tank (without surface diaphragm). The seismic response is investigated for the tank subjected to harmonic and real-earthquake excitations. The parameters considered for the analysis are the aspect ratio of the tank, eccentricity of the isolator, and thickness of the diaphragm. The seismic response quantities evaluated are base shear, sloshing displacement, and impulsive hydrodynamic pressure in the tank. Further, to study the effectiveness of the OSBI, the seismic responses of the tank subjected tri-directional components are compared with the two horizontal bi-directional components of the earthquakes. Also, the sloshing displacement with and without surface diaphragm in the non-isolated and base-isolated tanks are compared. From the results, it is observed that the OSBI system is efficient in mitigating the seismic responses in the tanks and the surface diaphragm is efficient in controlling the sloshing displacement. The superior performance of the proposed isolator depends on the design parameters, namely, eccentricity, and coefficient of rolling friction selected. The effectiveness of the surface diaphragm depends on the choice of material and thickness adopted.